Strategi Politik Air Hangat dalam Konflik Rusia - Ukraina - Haris, Umiyati; Niniek Paryati, Andi; Yohana Tuhalauruw, Evlecia (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
This study examines Russia’s warm-water political strategy within the geopolitical and geostrategic framework of the Eurasian region, using the Heartland Theory. The findings indicate that this strategy reflects Russia’s geopolitical interests, rooted in its geographical position and natural conditions. Crimea functions as both a symbol and a strategic tool for maintaining Russia’s access to the Black Sea and other warm-water routes. Within the Heartland Theory framework, control over Crimea reinforces Russia’s dominance across the land and maritime corridors connecting Asia and Europe. Beyond military and security concerns, Russia’s interests in Crimea are strongly tied to economic objectives, especially ensuring energy stability and securing vital trade routes. Crimea thus embodies the convergence of Russia’s territorial ambitions and geopolitical vision to gain permanent access to warm waters as a foundation for its global influence. The dynamics in the Black Sea further reveal complex interactions and rivalries among Russia, NATO, the European Union, and Turkey, positioning the region as a central arena for power competition and the rebalancing of influence across Eurasia. Keywords: strategy, warm-water politics, geopolitics, geostrategy, Heartland theory